Progression of Microstructural Damage in Spinocerebellar Ataxia Type 2: A Longitudinal DTI Study - Mascalchi, M.; Toschi, N.; Giannelli, M.; Ginestroni, A.; Della Nave, R.; Nicolai, E.; Bianchi, A.; Tessa, C.; Salvatore, E.; Aiello, M.; Soricelli, A.; Diciotti, S. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: The ability of DTI to track the progression of microstructural damage in patients with inherited ataxias has not been explored so far. We performed a longitudinal DTI study in patients with spinocerebellar ataxia type 2.MATERIALS AND METHODS: Ten patients with spinocerebellar ataxia type 2 and 16 healthy age-matched controls were examined twice with DTI (mean time between scans, 3.6 years [patients] and 3.3 years [controls]) on the same 1.5T MR scanner. Using tract-based spatial statistics, we analyzed changes in DTI-derived indices: mean diffusivity, axial diffusivity, radial diffusivity, fractional anisotropy, and mode of anisotropy.RESULTS: At baseline, the patients with spinocerebellar ataxia type 2, as compared with controls, showed numerous WM tracts with significantly increased mean diffusivity, axial diffusivity, and radial diffusivity and decreased fractional anisotropy and mode of anisotropy in the brain stem, cerebellar peduncles, cerebellum, cerebral hemisphere WM, corpus callosum, and thalami. Longitudinal analysis revealed changes in axial diffusivity and mode of anisotropy in patients with spinocerebellar ataxia type 2 that were significantly different than those in the controls. In patients with spinocerebellar ataxia type 2, axial diffusivity was increased in WM tracts of the right cerebral hemisphere and the corpus callosum, and the mode of anisotropy was extensively decreased in hemispheric cerebral WM, corpus callosum, internal capsules, cerebral peduncles, pons and left cerebellar peduncles, and WM of the left paramedian vermis. There was no correlation between the progression of changes in DTI-derived indices and clinical deterioration.CONCLUSIONS: DTI can reveal the progression of microstructural damage of WM fibers in the brains of patients with spinocerebellar ataxia type 2, and mode of anisotropy seems particularly sensitive to such changes. These results support the potential of DTI-derived indices as biomarkers of disease progression.ADaxial diffusivityFAfractional anisotropyMDmean diffusivityMOmode of anisotropyRDradial diffusivitySCA2spinocerebellar ataxia type 2TBSStract-based spatial statisticsMNIMontreal Neurological Institute